Consulta informada a los pueblos indígenas de los proyectos extractivistas que potencialmente afecten a sus comunidades - Burgos Merchán, Valeria Victoria (2017)
In Ecuador, indigenous communities enjoy the constitutional protection of the State, and of the fundamental rights inherent to their customs, soil, and survival within the areas where they have been established and developed as a society. The informed consultation on extractive projects, in the areas of protection. For this, it is estimated that it is the indigenous peoples and communities that bear the social and environmental cost of the extractive industries, obtaining little of the wealth generated….